Recueil de notices historiques lues dans les séances publiques de l'Académie Royale des Beaux-Arts - Quatremère de Quincy 1755-1849 (Paris Le Clerc, 1834)
Antoine-Chrysostome Quatremère de Quincy (1755-1849) was a French armchair archaeologist and architectural theorist, a Freemason, and an effective arts administrator and influential writer on art. The present anthology contains the biographies of architects, painters, composers (Paisiello, Monsigny, Méhul), sculptors, antiquarians, and engravers Quatremère de Quincy read as necrologies of deceased members at the Académie Royale des Beaux-Arts.
marbled endpages
Keywords: Paisiello, Giovanni -- 1740-1816; Méhul, Étienne Nicolas -- 1763-1817; Monsigny, Pierre-Alexandre -- 1729-1817; 19th Century (1801-1900); Music history; Composer; Biography; Fine art; Paris (France)